Utopie - Resta, Patrizia (EtnoAntropologia, 2014)
The paper presents the reasons why it’s necessary to open a debate about the crisis of anthropological studies in Italy, recalling the steps that over the years have led a weakening of the scientific thinking and a decrease of the anthropological teachings role within Italian Academy, as can be seen from the picture that emerges from the reconstruction offered by the ANVUR (National Agency for the Evaluation of the University and Research) for to the period 2010-2012. To this purpose, the paper compares the different positions expressed in the debate sponsored by A.I.S.E.A. on this issue and accepted in this volume, by focusing on the need, widely shared, of epistemological dimension recovery within the anthropological discipline, such as raising factor of interconnections that anthropological production permits.